P2 Pattern of delays in seeking legal judgements to withdraw life-sustaining therapy. (12th March 2018) - Harrison, L; Playfor, S
Abstract : Aims: In recent years legal judgements have being sought more frequently to allow withdrawal of life-sustaining therapy (LST) for patients in paediatric intensive care units (PICUs). Anecdotally, units can experience very long delays during the legal process. In order to clarify the current situation we have surveyed the medico-legal experience of UK PICUs over the last 5 years. Methods: A questionnaire was distributed to PICU Consultants with an interest in the medico-legal process in each UK PICU to collect relevant data. Results: Data was returned from 26 centres and a total of 15 cases were identified. 73% of children were under 1 year of age, 87% of children were under the age of 2 years. The interval between notifying the Trust medico-legal department and a first court date varied from 2 days to 16 weeks and the overall delay between notifying the Trust medico-legal department and obtaining a final judgement varied with a biphasic distribution; 31% of cases were dealt with as emergencies and concluded in less than 2 weeks, 61% of cases, considered more 'stable' took up to 6 months to resolve. 8% of cases took longer than 6 months to resolve, with the longest taking 14 months. Conclusion: Our findings demonstrate that whilst a minority of cases are dealt with promptly; around two-thirds of cases include considerable time delays. Prolonged admissions in this context result in extended periods of invasive treatment which are not in children's best interests, considerable disruption to families and siblings, and enormous stresses on PICU staff. In addition there is considerable financial cost in terms of resources and legal fees. PICU staff should engage with the Family Division of the High Court to develop a fast-track process for dealing with these cases.